Contribuições da eletroquímica molecular para a química medicinal: o caso das quinonas híbridas calcogenadas e halogenadas - Silva, Thaissa Lúcio (2017)
Molecular electrochemistry has proved to be very useful for characterizing redox reactions and deciphering chemical reaction mechanisms that are associated with electron transfer. It correlates strongly with redox-based medicine. In this study, we investigated the electrochemical behavior of pterocarpanquinones and selenoquinones, in protic and aprotic media, in the absence and presence of oxygen, in order to obtain data regarding their reduction mechanisms, reactivity with oxygen, the analysis of the stability of the electrogenerated intermediates and interactions with biological targets, like DNA. In typical measurements, CVs were recorded in aprotic medium (DMF + TBAPF6) to resemble the cell membrane environment. On the other hand, protic medium mimics the hydrophilic regions of the biological matrixes. This work shows cases of successful pharmacoelectrochemical investigations. In the first case, we investigate the electrochemical behavior of LQB-118, a pterocarpanquinone, which is anticancer and parasiticidal, with biological mechanisms of action related to the formation of ROS and interaction with DNA, among others. The cyclic voltammogram (VC) for LQB-118 in aprotic medium exhibits, at least, four waves. The first two are related to the usual reduction of quinones. The presence of additional waves suggests the clivage of the heterocyclic rings and the generation of additional reducible systems. A spectroelectrochemical investigation revealed the appearance of new absorption bands, which suggest the formation of the transient quinonamethide (QM). The QM was captured with thiophenol. In addition, electrochemical experiments were performed in the presence and absence of oxygen to verify the reactivity with oxygen, after the reduction of LQB-118 and its derivatives, with positive results. Studies with the ssDNA biosensor in solution showed positive interaction with LQB-118 and its electrogenerated products. The interaction of LQB-118 with CT-DNA was also evidenced by the fluorescence quenching technique. In the second case, CV was used to investigate the electrochemical behaviour of the antitumor selenoquinones. The obtained profiles confirmed the presence of two individual redox centres. All the compounds had shown electrochemical activity in the cathodic and anodic portions of the CVs. We also studied the behaviour of the compounds in protic medium. Electrochemical methods do well to predict the mechanism for adduct formation, structural rearrangement, generation of reactive oxigen species of pterocarpanquinones and appear well-adapted to explore redox pathways of all the compounds in vitro to be correlated to in vivo studies.